Two novel amide alkaloids from Portulaca oleracea L. and their anti-inflammatory activities. Issue 21 (1st November 2022) - Lan, Xiujuan; Ying, Ziyue; Guo, Shengnan; Duan, Yang; Cui, Xinyu; Leng, Aijing; Ying, Xixiang
Abstract: In this article, two novel amide alkaloids were identified as ( E )-3-(4-hydroxy-3-methoxyphenyl)-1-(5-hydroxy-6-((3, 4, 5-trihydroxy-6-(hydroxymethyl)tetrahydro-2 H -pyran-2-yl)oxy)-1 H -indol-1-yl)prop-2-en-1-one (1 ) and ( E )-1-(5-hydroxy-6-((3, 4, 5-trihydroxy-6-(hydroxymethyl)tetrahydro-2 H -pyran-2-yl)oxy)-1 H -indol-1-yl)-3-(4-hydroxyphenyl)prop-2-en-1-one (2 ), the two compounds were named oleraindole E and oleraindole F, respectively. The structures were elucidated using 1D and 2D NMR and HR-ESI-TOF-MS spectra. Additionally, the anti-inflammatory activities were evaluated on RAW264.7 cells induced by LPS, compounds 1 and 2 exhibited anti-inflammatory activities at 20 μM. Graphical Abstract: UF0001